(untitled) (World Bulletin of Management and Law, 2024)
This article examines the essence of the right to the inviolability of the home, and identifies the subjects of this right. A comparative legal analysis of the right to privacy of housing with the right to housing, the right to privacy, and the right to inviolability of property was carried out.